Peran Learning Organization Dalam Meningkatkan Kinerja Dosen Di Universitas Bojonegoro - Maghfiroh, Inayatul; Amaliyah, Istiqfirul Hidayati; Fadhila, Leni Nur; Hendani, Hanna Putri; Anggraini, Lucia Dwi Rahma (YPI Ulul Albab, 2025)
The aim of the research is to explore how Learning Organization can affect the performance of lecturers at Bojonegoro University. Learning Organization is a concept introduced by Peter Senge in